Implementation of the Adiwiyata School in Improving the Quality of Public Elementary School Education - Ainur Rahman; Sedya Santosa; Muhammad Syaikhul Basyir; Ika Nur'aini; Zainal Arifin (STAI Hubbulwathan Duri, 2023)
This study was carried out at a public elementary school in Krapyak Wetan with the aim of investigating the implementation of the Adiwiyata pilot school in enhancing the educational quality in relation to the Adiwiyata school programme policies. The study also examined the execution of the Adiwiyata school programme, as well as the factors that support or hinder its implementation. The employed methodology is a qualitative approach with a descriptive orientation. Data collection methods encompassing observation, in-depth interviews, and documenting. The data sources include of the school principal, school treasurer, Adiwiyata team members, and teachers. The process of data analysis involved data reduction, data display, and data verification. The research yielded recognition for the Adiwiyata school at the district level in Bantul. Additionally, it led to the implementation of various programmes such as daily plastic-free cleaning activities, the establishment of healthy and food-safe canteens, the implementation of a simple school wastewater treatment system (IPAL), compost processing programmes, the installation of composters, the establishment of hydroponics systems, the construction of greenhouses, the creation of biopores for planting, the utilisation of ablution water waste, and the implementation of the 3R recycling principle (reuse, reduce, and recycle) among others. The programme is executed by including many components, such as the adoption of eco-friendly policies, implementation of an eco-friendly curriculum, engagement in participatory environmental activities, and efficient management of eco-friendly supporting infrastructure. Hydroponics, greenhouses, biopore planting, ablution water waste, 3R recycling (reuse, reduce and recycle), and other related methods and practises. The programme is executed by incorporating components such as eco-friendly policies, implementation of an eco-friendly curriculum, participatory environmental activities, and management of eco-friendly supporting facilities. Hydroponics, greenhouses, biopore planting, ablution water waste, 3R recycling (reuse, reduce, and recycle), and other related practises. The programme is executed by incorporating components such as eco-friendly policies, implementation of an eco-friendly curriculum, participatory environmental activities, and management of eco-friendly supporting facilities.